Catastrophic and Impoverishing Health Expenditure in Tehran Urban Population - S Bagheri faradonb (مدیریت سلامت, 2016)
Introduction: Measurement of financial support for health services is determined by household out of pocket expenditure for health which is associated with two approaches: catastrophic and impoverishing health expenditures.